Antibacterial Activity of Acacia Catechu Seed Against Urinary Tract Pathogens (Indian Journal of Public Health Research & Development, 2020)
Aim: The aim of the study is to investigate the antibacterial efficacy of the Acacia catechu seed extractagainst selected Urinary tract pathogensBackground :Acacia catechu is known as Cutch tree.This plant has following medicinal properties:Astringent, Bactericidal, Refrigerant, Stimulant, Masticator, Expectorant. Acacia catechu seeds are flat, darkbrown and measure 5-8 mm in diameter. The seeds are edible and the extract is useful in the treatment ofmany medical conditions in the Ayurveda.Reason: Urinary tract infections are most common infection caused in woman, hence this study candetermine the antibacterial effectiveness among the pathogens causing urinary tract infections.
Keywords: Acacia catechu, Medicinal, Urinary tract infection, Antibacterial.